Penerapan Personal Hygiene Pada Penjamah Makanan di Pondok Pesantren Kecamatan Biring Kanaya Kota Makassar - Nildawati Nildawati; Hasbi Ibrahim; Fatmawaty Mallapiang; Khansaa Afifah M; Emmi Bujawati (POLTEKKES KEMENKES MANADO, 2020)
Personal hygiene will have an impact on the food produced by a food handler. To carry out its functions, Islamic boarding schools have a food management system which is carried out by food handlers. This study aims to see the personal hygiene of food handlers at the Pondok Pesantren, Biringkanaya District, Makassar City. The research method used is descriptive research. The sampling method used was total sampling with a total of 30 samples. The results of the study prove that of the 30 respondents, 100% in good category for the application of personal hygiene. The work period of less than or 5 years was 17 respondents (56.7%) and respondents with a working period of more than 5 years were 13 respondents (43.3%). Of the 30 respondents (100%) only 1 respondent (33%) had work experience as food handlers in another place, namely, for 15 years at other Islamic boarding schools, 29 respondents (96.7%) had no work experience as food handlers. The application of personal hygiene to food handlers is fairly good, all respondents have good personal hygiene, but the application of washing hands before and after work and after leaving the bathroom is not in accordance with good and correct handwashing procedures according to WHO or the Indonesian Ministry of Health, this is evidenced by the unavailability of handwashing facilities. Provision of education, media-related information personal hygiene should be performed periodically to increase awareness of food handlers, as well as providing training, SOP, APD, P3K box, and checks periodically